Role of lymphadenectomy during primary surgery for kidney cancer - Bekku, Kensuke; Kawada, Tatsushi; Yanagisawa, Takafumi; Karakiewicz, Pierre I; Shariat, Shahrokh F (Current opinion in urology, 2023)
PURPOSE OF REVIEW: Lymph node dissection (LND) during radical nephrectomy (RN) for renal cell carcinoma (RCC) is not considered as a standard. The emergence of robot-assisted surgery and effective immune checkpoint inhibitors (ICI) in recent years may change this and lymph node (LN) staging has become easier and has a clinical impact. In this review, we aimed to reconsider the role of LND today. RECENT FINDINGS: Although the extent of LND has still not been well established, removal of more LN seems to provide better oncologic outcomes for a select group of patients with high-risk factors such as clinical T3-4. Adjuvant therapy using pembrolizumab has been shown to improve disease free survival if complete resection of metastatic lesions as well as the primary site is obtained in combination. Robot assisted RN for localized RCC has been widespread and the studies regarding LND for RCC has been recently appeared. SUMMARY: The staging and surgical benefits and its extent of LND during RN for RCC remains unclear, but it is becoming increasingly important. Technologies that allow an easier LND and adjuvant ICI that improve survival in LN-positive patients are engaging the role of LND, a procedure that was needed, but almost never done, is now indicated sometimes. Now, the goal is to identify the clinical and molecular imaging tools that can help identify with sufficient accuracy who needs a LND and which LNs to remove in a targeted personalized approach.
Keywords: lymfadenektomie; lymfatické uzliny; Neoplasm Staging; staging nádorů; Carcinoma, Renal Cell; nádory ledvin; Lymph Node Excision; Lymph Nodes; karcinom z renálních buněk; Humans; Kidney Neoplasms; lidé